Forvaltningen af publikums ubehag: FIX&FOXY som politisk konfrontationskunst - Schultz, Laura Luise (Peripeti, 2022)
Forvaltningen af publikums ubehag. FIX&FOXY som politisk konfrontationskunst by Laura Luise Schultz. She describes the approach to the audience in various of performances and highlights, that a central feature of FIX&FOXY's political remediation is their sophisticated engagement with the audience and managing of the audience's discomfort.